Marketing strategy of Alza.cz a.s. - Matoušek, Martin (2022)
The first part of the bachelor thesis focuses on the theory of marketing and marketing strategies. The second part is devoted to the survey of the company Alza.cz a.s. in terms of marketing strategy and its possible prospects for the future. In the third part, methodological research in the form of a questionnaire survey is processed and interpreted, which is then evaluated in the form of a recommendation.